Atomic-Level Insights Into the Initial Oxidative Crystallization of Si(100) to Periodic SiOx - Srivastava, Divya; Lahti, Antti; Kokko, Kalevi; Punkkinen, Marko; Laukkanen, Pekka (Wiley-VCH, 2026)
MD Simulations based on force fields and first-principles calculations based on density functional theory have been employed to investigate the initial stages of oxidation on silicon (100) surfaces exhibiting a p(2 × 2) reconstruction when exposed to atomic oxygen. Our results reveal that, when oxygen atoms are sequentially added to energetically preferred sites on the p(2 × 2) reconstructed Si(100) surface, the lattice maintains its crystallinity for up to three layers, in contrast to the typically observed disordered surface oxide. Detailed atomic and electronic structures of the crystalline SiOx/Si are presented, which provide a starting point model for the recent measurements of crystalline SiOx/Si formed under controlled oxidation conditions.